Farklılıkların etkin yönetiminde kullanılan halkla ilişkiler stratejileri: bir kamu kurumu olarak emniyet teşkilatı - Duman, Mehmet Deman (My University, 2013)
Kurumlarda çalışan personelin birbirinden farklılığı yeni bir husus olarak ortaya çıkmamıştır. Bir kurumda çalışan insanlar; yaş, etnik köken, medeni hal, eğitim, cinsiyet vb. gibi yönlerden birbirinden farklı olması çok tabidir. Kurumlar, bünyelerinde barındırdıkları çalışanların farklı yönlerinden yararlandıkları ölçüde başarılı olurlar. Günümüzde; sosyal, teknolojik, iletişim, bilim, politika gibi alanlarda yaşanan değişim ve küreselleşme ile birlikte, kurumlarında stratejilerinde ve felsefelerinde değişim yaşanmıştır. Dünyada yaşanan bu değişimlerden sonra, Kurumlarda tek tip çalışan yerine farklı özelliklere sahip çalışanları bünyelerinde çalıştırmaktadırlar. Farklılıkların Yönetimi, kurumlarda çalışan insanların farklı özelliklerine ( yaş, cinsiyet, eğitim, etnik köken vb.) karşı hoşgörülü olmayı ve bu farklılıklardan yararlanarak kuruma başarı getirmeyi hedeflemektedir. Kısacası farklılıkların yönetimi, çalışanların farklılıklarını bir olumsuzluk olarak değil, bir zenginlik olarak görmektedir. Kurumlar farklılıkların yönetimi konusunda başarılı olabilmek için halkla ilişkiler faaliyetlerinden çokça faydalanmaları gerekir. Tez üç ana bölümden oluşmaktadır. Birinci bölümde; farklılık kavramı, farklılıkların boyutları, farklılıkların yönetimi kavramı, farklılıkların yönetiminin tarihsel gelişimi, farklılıkları yönetmenin faydaları ve halkla ilişkiler konusundan bahsedilmiştir. Tezin ikinci bölümünde; farklılıkların yönetilmesinde halkla ilişkiler, farklılıkların yönetilmesinde kullanılan halkla ilişkiler faaliyetlerinin kurumsal getirileri konuları detaylı bir şekilde incelenmiştir. Tezin son bölümü olan üçüncü bölümde, Emniyet teşkilatı üzerinde farklılıkların yönetimi konusu ile bağlantılı olarak yapılan araştırma ile ilgili bulgulara ve değerlendirmelere yer verilmiştir. Anahtar Kavramlar: Farklılık, Farklılıkların Yönetimi, Halkla İlişkiler, Emniyet Teşkilatı

The difference of the personnel working in the organizations from each others did not occur as a new matter. It is considerably natural for the people who are employed in an organization to be different from each others with respect to many aspects such as age, ethnical origin, marital status, education, gender etc. The organizations become successful to the extent they could benefit from different aspects of the employees that they accommodate within their own structures. Today; with the change and globalization experienced on the areas such as social, technological, communication, science and politics, a change is experienced in the strategies and philosophies of the organizations too. After these changes which are experienced in the world, the Organizations also employ employees having different characteristics instead of prototype employees in the organizations. Management of Differences targets at tolerating the different characteristics of the people employed in the organizations (such as age, gender, education, ethnical origin, etc) and bringing success to the organization by means of benefiting from these differences. In short, the management of differences considers the differences of the employees not a negative aspect but richness instead. It is necessary for the organizations to benefit from the public relation activities greatly in order to be successful on the subject of management of differences. The thesis is composed of three (3) main chapters. In the first chapter; concept of difference, dimensions of differences, concept of management of differences, historical development of the management of differences, benefits of management of differences and the subject of public relations are mentioned. In the second chapter of the thesis; the subjects of public relations in managing the differences and the organizational benefits of the public relations activities which are utilized in managing the differences are examined in full details. In the third and last chapter of the thesis, the findings and evaluations relating to the research carried out in connection with the subject of management of differences on the Police Establishment are mentioned. fference, Management of Differences, Public Relations, Police Establishment.
Keywords: Farklılık, İş yerinde; Halkla İlişkiler; Örgütsel Değişim